KARAKTERISTIK FISIK MIKROPARTIKEL KUERSETIN DENGAN KOMBINASI KITOSAN-NATRIUM TRIPOLIFOSFAT MENGGUNAKAN METODE ORIFICE IONIC GELATION - Aditya Trias Pradana; Roisah Nawatila; Muhammad Rifani Rachman (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Antioxidants are compounds to resist free radicals. The natural antioxidant group that is currently being developed is the flavonoid group, one of which is quercetin. Quercetin has a low solubility, so it can be increased by reducing the particle size. This study aims to determine the differences that are influenced by the combination of chitosan polymer and sodium tripolyphosphate as matrix forming quercetin microparticles on the physical characteristics of the results made using the orifice ionic gelation method. The resulting preparation showed a particle size of 1326.33 nm; 3497.33 nm; and 6000 nm at various concentrations of 0.2% chitosan and 0.1%; 0.2%; and 0.3% sodium tripolyphosphate, respectively. The Fourier Transform Infrared (FTIR) results showed that there was no change in the marker group on quercetin and an ionic bond was formed between chitosan and sodium tripolyphosphate. The X-ray Diffractometer (XRD) results showed that the crystalline structure of quercetin changed to become more amorphous. Although the Scanning Electron Microscope (SEM) results, it is seen that the quercetin microparticles produced are needle-shaped, especially when the concentration of sodium tripolyphosphate is increased. Based on the results of these physical characteristics, it can be proven that the microparticle was formed at various concentrations of the polymer concentration combination with the best characteristics are on 0.2% chitosan and 0.1% sodium tripolyphosphate concentration.